Effect of Corporate Governance on the Performance of Information Technology (IT) Firms in the UK - xu, shaopan (2017)
The major objective of this research is to identify and analyze the probable relationship between the various aspects of the corporate governance and the financial performance of the firms in the information technology sector in the United Kingdom. In order to assess the effect of corporate governance on the performance of the firm, the study has formulated a number of objectives around which the study revolves around. The first objective of the study pertains to an analysis of the relationship between the size of the board of directors and the financial performance in the case of IT firms in the United Kingdom. The second objective aims at evaluating the relationship between the CEO Duality and the financial performance in the case of IT firms in the United Kingdom. Lastly, the third objective aims at analyzing the relationship between the composition of the board and the financial performance in the case of IT firms in the United Kingdom. The methodology employed for this study includes a combination of both qualitative as well as quantitative approaches to data analysis. The quantitative analysis includes the application of statistical tests on the data while the qualitative analysis includes the analysis of the impact of CEO duality on the financial performance of the firms in the case of Turkey and Hong Kong. The results of the study depict an existence of a significantly positive relationship between the financial performance and the Board Composition and the CEO Duality in the case of the IT firms in the UK, while there exists a negative relationship between the Board size and the financial performance of the IT firms in the UK.